First observation of CP violation in the decays of B0s mesons - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; Grünberg, Oliver; et al. (Physical review letters, 2013)
Using pp collision data corresponding to an integrated luminosity of 1.0 fb−1 and collected by LHCb in 2011 at a center-of-mass energy of 7 TeV, we report the measurement of direct CP violation in B0s→K−π+ decays, ACP(B0s→K−π+)=0.27±0.04 (stat)±0.01 (syst), with significance exceeding 5 standard deviations. This is the first observation of CP violation in the decays of B0s mesons. Furthermore, we provide an improved determination of direct CP violation in B0→K+π− decays, ACP(B0→K+π−)=−0.080±0.007 (stat)±0.003 (syst), which is the most precise measurement of this quantity to date.
Im Titel ist "0" hochgestellt und "s" tiefgestellt
LHCb Collaboration: R. Aaij, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, M. Britsch, A. Di Canto, F. Dordei, C. Färber, M. Fontana, E. Gersabeck, O. Grünberg, S. Hansmann-Menzemer, T. Hartmann, A. Jaeger, K. Kreplin, G. Krocker, B. Leverington, C. Linn, J. Marks, M. Meissner, T. Nikodem, D. Popov, M. Schmelling, P. Seyfert, S. Stahl, J. van Tilburg, U. Uwer, D. Volyanskyy, C. Voß, H. Voss, R. Waldi, S. Wandernoth, D. Wiedner, M. Zavertyaev, A. Zhelezov und weitere 597
Gesehen am 21.04.2021